Carbon deposition using various solid fuels for ironmaking applications - Cahyono, Rochim B.; Rozhan, Alya Naili; Yasuda, Naoto; Nomura, Takahiro; Purwanto, Hadi; Akiyama, Tomohiro (American Chemical Society (ACS Publications), 2013)
In this paper, we describe an innovative process involving iron reduction through chemical vapor deposition for applications in the ironmaking industry. In our experiment, we produced tar vapors from pyrolysis of various solid fuels, including high-grade bituminous coal (HGC), low-grade lignite coal (LGC), and biomass palm kernel shell (PKS), and decomposed these vapors into gases, carbon, and light hydrocarbon. Carbon was deposited within the pores of pisolite ore (low-grade ore), which became porous during the dehydration process at 450 °C. We determined that the amount of tar produced during pyrolysis strongly affected carbon deposition, and HGC produced the highest carbon deposition because of its large tar product. In addition to tar amount, surface area and pore volume also played important roles in this process. PKS had the highest ratio of deposited carbon because it produced the smallest quantities of reacted tar and, consequently, the largest numbers of vacant pores. The amount of carbon deposition decreased at higher temperatures because tar was easily converted to a gaseous phase. The deposited carbon within iron ore showed potential as a reducing agent because it was highly reactive and reduced at lower temperatures. Carbon deposited within iron pores dramatically reduced the contact distance between the iron ore and carbon. Thus, these results show that our proposed methodology could have important applications as an alternative low-energy approach for producing metallic iron using low-grade materials.